2012
DOI: 10.1590/s0100-204x2012001200012
|View full text |Cite
|
Sign up to set email alerts
|

Seleção e caracterização de estirpes de Bacillus thuringiensis eficientes contra a Diatraea saccharalis (Lepidoptera: Crambidae)

Abstract: Resumo -O objetivo deste trabalho foi selecionar e caracterizar estirpes nativas de Bacillus thuringiensis tóxicas a Diatraea saccharalis (Lepidoptera: Crambidae). Cento e seis estirpes pertencentes ao Banco Selection and characterization of Bacillus thuringiensis efficient strains against Diatraea saccharalis (Lepidoptera: Crambidae)Abstract -The objective of this work was to select and characterize native strains of Bacillus thuringiensis toxic to Diatraea saccharalis (Lepidoptera: Crambidae). A hundred-and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
15

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 26 publications
1
3
0
15
Order By: Relevance
“…Selecting and characterizing Brazilian strains of Bacillus thuringiensis toxic to P. xylostella, Praça (2012) found that the B. thuringiensis strains S1905 and S2122 caused 100% of mortality in caterpillars in the 3º instar of Plutella xylostella in evaluation performed 48 h after caterpillars had been exposed to selective bioassays, whereas S2124 caused 58.33% of mortality after the same period and 98.33% of mortality after 96 h. In these cases, CL 50 values ranged from 2.33 to 4.84 ng/mL, with results of toxicity similar to the control. Viana et al (2009) Recently, Macedo et al (2012), selecting and characterizing native strains of B. thuringiensis toxic to Diatraea saccharalis (Lepidoptera: Crambidae), observed that the strains causing more than 75% of mortality after dilution of 50 times were: S602, S1264 and S1301. From these strains, the most toxic to D. saccharalis were S602 and S1264, with statistically similar CL 50 values, but different from S1301.…”
Section: Endophytic Bacteria In the Control Of Pest Insects In Agricumentioning
confidence: 99%
“…Selecting and characterizing Brazilian strains of Bacillus thuringiensis toxic to P. xylostella, Praça (2012) found that the B. thuringiensis strains S1905 and S2122 caused 100% of mortality in caterpillars in the 3º instar of Plutella xylostella in evaluation performed 48 h after caterpillars had been exposed to selective bioassays, whereas S2124 caused 58.33% of mortality after the same period and 98.33% of mortality after 96 h. In these cases, CL 50 values ranged from 2.33 to 4.84 ng/mL, with results of toxicity similar to the control. Viana et al (2009) Recently, Macedo et al (2012), selecting and characterizing native strains of B. thuringiensis toxic to Diatraea saccharalis (Lepidoptera: Crambidae), observed that the strains causing more than 75% of mortality after dilution of 50 times were: S602, S1264 and S1301. From these strains, the most toxic to D. saccharalis were S602 and S1264, with statistically similar CL 50 values, but different from S1301.…”
Section: Endophytic Bacteria In the Control Of Pest Insects In Agricumentioning
confidence: 99%
“…, leguminosas (TANUJA et al, 2003), amendoim (WANG et al, 2014) e ainda como inseticida sistêmico (PRAÇA et al, 2012) pode vir a ser uma alternativa interessante.…”
Section: Lista De Abreviaturas E Siglasunclassified
“…(ARONSON et al, 1986 (SHISHIDO et al, 1999) e B. thuringiensis (MONNERAT et al, 2003;PRAÇA et al, 2012) e também promoveram o crescimento vegetal (GOMES et al, 2003;TANUJA et al, 2013;WANG et al, 2014).…”
Section: Helicoverpa Armigeraunclassified
See 2 more Smart Citations